CASE BASED REASONINGUNTUK MENDIAGNOSIS GIZI BURUK PADA ANAKUSIA 0-5 TAHUN MENGGUNAKAN METODE COSINE SIMILARITY - Derwin Rony Sina; Meiton Boru; Marselina Elisabeth Soinbala (Universitas Nusa Cendana, 2019)
Case Based Reasoning (CBR) method is one method to build a system with new case decision based on solution from previous cases by calculating similarity level. The calculation of similarity values ​​using the Cosinr Similarity with threshold 80%. This system can diagnose 3 diseases based on 23 existing symptoms.Based on the results of the test case obtained the results: the system can take back the old case is appropriate and has used the formulation of Naïve Bayes method to distribution of disease class and used the formulation of Cosine Similarity method to calculation correctly indicated with 100% accuracy, and use 122 cases. . Based on the test of 40 new cases obtained system accuracy of 80%.